Intention And Motivation Toward Entrepreneurship - Mustapha, Musramaini; Mohamad, Siti Aishah; Azer, Ilyani (Journal of Technology Management and Business, 2014)
Entrepreneurship has become an important agenda in the Malaysian Education System. The Malaysian government has started to embark on entrepreneurship development among students. It is proven with huge budget allocated by the Ministry of Higher Education (MOHE) in order to drive entrepreneurship activities among the students in the universities. All activities conducted are to increase students’ intentions and motivation to be entrepreneurs. It is very important to the university to know about the final year students’ intentions to choose entrepreneurship as their profession in the future. MOHE targets about 6,000 graduates to become entrepreneurs in 2013-2015 from the implementation of Entrepreneurial Strategic Plans 2013-2015. Due to that, this study was conducted to identify the intentions and motivations toward entrepreneurship among the final year students from two UiTM campuses (UiTM Pahang and UiTM Melaka). The overall results showed the intentions to be entrepreneurs among the students from two campuses were positive. UiTM Pahang final year students were motivated to be entrepreneurs because they wanted to be their own boss, and the UiTM Melaka final year students wanted to realize their own dreams to become entrepreneurs. The students’ intentions and motivations towards entrepreneurship are very important not only to the universities, but also for the nation and the country as a whole. These findings may assist UiTM Pahang and UiTM Melaka to create more opportunities for their students to get involved in businesses by continually supporting entrepreneurship development. Besides, the aim of MOHE to produce 6,000 entrepreneurs within 2013-2015 can be achieved.